2013
DOI: 10.1021/cg301299e
|View full text |Cite
|
Sign up to set email alerts
|

A Supramolecular Assembly Formed by Heteroassociation of Ciprofloxacin and Norfloxacin in the Solid State: Co-Crystal Synthesis and Characterization

Abstract: The interaction in the solid state between ciprofloxacin (CIP) and norfloxacin (NOR) was investigated and a new multicomponent molecular complex (COP) was obtained and characterized. It is composed of equimolar quantities of both compounds, according to TLC and 1 H NMR data. As single-crystal X-ray analysis showed, COP crystallizes in the triclinic system, space group P(1̅ ). The asymmetric unit comprises three independent zwitterions (A, B, and C) with contributions of both CIP and NOR, as well as 14.6 water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In addition, the so-called drug-drug salt forms of CIP with non-steroidal anti-inflammatory drugs, diflunisal and indoprofen, have recently been obtained and characterized (Bag et al, 2014). While, Vitorino et al (2013) were able to isolate a multicomponent molecular complex comprising ciprofloxacin and norfloxacin ions in the solid state. It has recently been reported that new ciprofloxacin salts enhance the aqueous solubility and simultaneously influence the octanol-water partition coefficient of the drug, which allows the tuning of relevant pharmacological properties by the counter ion alteration (Florindo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the so-called drug-drug salt forms of CIP with non-steroidal anti-inflammatory drugs, diflunisal and indoprofen, have recently been obtained and characterized (Bag et al, 2014). While, Vitorino et al (2013) were able to isolate a multicomponent molecular complex comprising ciprofloxacin and norfloxacin ions in the solid state. It has recently been reported that new ciprofloxacin salts enhance the aqueous solubility and simultaneously influence the octanol-water partition coefficient of the drug, which allows the tuning of relevant pharmacological properties by the counter ion alteration (Florindo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained solid was analyzed by melting point (m.p), 1 H MNR, Hot Stage Microscopy, Differential Scanning Calorimetry (DSC), Thermogravimetry, Powder X-ray Diffraction (PXRD) and DRIFT. 1 The antibacterial effect of NOR, SMX and NOR-SMX was evaluated against Escherichia coli ATCC 25922 using the macrodilution method and checkerboard. The minimum inhibitory concentration (MIC) and the fractional inhibitory concentration (CIF) were determined.…”
Section: Supramolecular Complex Of Norfloxacin and Sulfamethoxazole: mentioning
confidence: 99%
“…19) In this co-crystal phase there are three independent drug molecule sites which accommodate different proportions of CIP and NOR such that the overall stoichiometry is 1 : 1. In addition to the presence of strong charge-assisted N + -H ...…”
Section: )mentioning
confidence: 99%
“…those of COP and a triclinic modification of CIP). [19][20][21] Figure 1 highlights the above molecular interactions as they occur in the COP co-crystal phase.…”
mentioning
confidence: 99%